Differential effects of novel wasp toxin on rat hippocampal interneurons - Miyawaki, T.; Tsubokawa, H.; Yokota, H.; Oguro, K.; Konno, K.; Masuzawa, T.; Kawai, N. (Elsevier B.V., 2002)
We studied the effects of a wasp toxin beta-pompilidotoxin (beta-PMTX) on rat hippocampal CA1 interneurons by the current-clamp technique. The firing patterns of pyramidal neurons and pyramidale interneurons were not affected by beta-PMTX, but in oriens and radiatum interneurons, beta-PMTX converted the action potentials to prolonged depolarizing potentials by slowing the inactivation of Na+ channels. In lacunosum moleculare interneurons, beta-PMTX induced initial bursting spikes followed by block of succeeding spikes. Comparison of beta-PMTX with a sea anemone toxin, ATX 11, revealed that ATX 11 altered the firing properties of pyramidal neurons and pyramidale interneurons that were unchanged by beta-PMTX. Our results suggest that beta-PMTX modulates Na+ currents in CAl interneurons differently in various CAl neurons and the toxin is useful to classify Na+ channel subtypes. (C) 2002 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: interneuron; sodium channel; inactivation; wasp toxin; pompilidotoxin; sea anemone toxin